E PluriBus Unum: High Performance Connectivity On Buses - Mahajan, Ratul; Agarwal, Sharad; Padhye, Jitu; Zill, Brian (2008)
We present PluriBus, a system to provide high-performance Internet access on-board moving vehicles. It seamlessly combines multiple wide-area wireless paths that individually tend to be lossy and high-delay. PluriBus employs opportunistic erasure coding, a novel technique to use spare capacity along any path to mask losses from end hosts. It sends erasure coded packets only when there is an opening in a path's spare capacity, so that coded packets do not delay or steal capacity from ordinary data packets. Packets are coded using Evolution codes that we have developed to greedily maximize the expected number of data packets recovered with each coded packet. We have deployed PluriBus on two buses. Our experiments show that it reduces the median flow completion time by a factor of 2.5, compared to an existing method for spreading traffic across multiple paths.